Change the World for a Fiver - Harvey, Eugenie (Short Books Ltd., 2004)
This is a book of simple, everyday actions which reckon pretty much all of us can do. Change the World for a Fiver has been published to mark the launch of We Are What We Do, a project of community links.
Keywords: Environmental Conservation & Protection; Juvenile Nonfiction; Science & Nature